1990
DOI: 10.1161/01.cir.82.4.1316
|View full text |Cite
|
Sign up to set email alerts
|

Doppler assessment of right ventricular filling in a normal population. Comparison with left ventricular filling dynamics.

Abstract: To examine whether alterations in right ventricular filling dynamics occur with increasing age and to compare right and left ventricular filling in normal subjects, pulsed Doppler echocardiographic studies were performed at the tricuspid and mitral anuli in 50 normal volunteers (23 males and 27 females) with an age range of 5-66 years. An age-related decrease in peak early filling velocity, increase in peak late velocity, and augmentation in the late/early ratio of peak velocities at the tricuspid anulus were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
2
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 32 publications
8
48
2
3
Order By: Relevance
“…This is particularly problematic, as subjects with RV pathology might be expected to have compensatory higher heart rates than subjects with normal RV performance. The heart rate dependency of tricuspid Doppler parameters includes a rate-related increase in peak A wave velocity and atrial filling fraction, which is consistent with prior reports in normal subjects [2, 3, 4]. The current study extends the observation of heart rate dependency to patients with a variety of RV pathological states.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is particularly problematic, as subjects with RV pathology might be expected to have compensatory higher heart rates than subjects with normal RV performance. The heart rate dependency of tricuspid Doppler parameters includes a rate-related increase in peak A wave velocity and atrial filling fraction, which is consistent with prior reports in normal subjects [2, 3, 4]. The current study extends the observation of heart rate dependency to patients with a variety of RV pathological states.…”
Section: Discussionsupporting
confidence: 91%
“…In normal subjects, the age dependency of the tricuspid peak E velocity, E/A ratios and atrial filling fraction has been previously described in some reports [1, 2, 3, 4]but not in others [5, 6]. This study has shown that this age dependency is also present in subjects with a variety of RV pathologic findings.…”
Section: Discussionsupporting
confidence: 66%
“…A relação E/A diminui cerca de 0,1 pontos por década. 117,141,149,150 A inspiração causa um aumento da onda E, e, portanto, um aumento da relação E/A. A taquicardia causa um aumento da onda E, porém um aumento relativamente maior na onda A, e consequentemente uma diminuição da relação E/A.…”
Section: B Medidas Para Avaliação Da Disfunção Diastólicaunclassified
“…A taquicardia causa um aumento da onda E, porém um aumento relativamente maior na onda A, e consequentemente uma diminuição da relação E/A. 141,150,15 Quando comparamos os parâmetros do Doppler entre pacientes ou no mesmo paciente, o efeito das variáveis hemodinâmicas sobre os parâmetros estudados deve ser levado em conta. Em função das suas paredes muito finas, o VD é extremamente sensível a elevações da pós carga (estresse de parede), especialmente na presença de doenças que afetem o miocárdio do VD, como isquemia e infarto do miocárdio.…”
Section: B Medidas Para Avaliação Da Disfunção Diastólicaunclassified
“…Categorical variables were compared using the w 2 -test. Because the parameters of systolic and diastolic function are in a great degree influenced by age, [12][13][14] for purposes of univariate analysis these parameters were adjusted to an age of 45 years according to the formula adjusted parameter ¼ measured parameter-b (age-45), where b is the coefficient of the linear regression between measured parameter and age. The ability of MAVPD À1 mitral E/A ratio À1 and LV mass index to discriminate between subjects who developed HTN and those who remained normotensive at follow-up was evaluated by receiver operating characteristic (ROC) curves with calculation of areas under the curves (AUC) of sensitivity plotted vs 1-specificity.…”
Section: Left Ventricular Long-axis Function Predicts Hypertension D mentioning
confidence: 99%